End-user perceptions of success and failure: narratives from a natural laboratory of rural electrification projects in Malaysian Borneo - VAN GEVELT, Terry (Institutional Knowledge at Singapore Management University, 2020)
Located deep in the Kelabit Highlands in Malaysian Borneo, the remote town of Bario offers us a natural laboratory of rural electrification projects through which to understand end-user perceptions of success and failure, and the factors that contribute to these perceptions. We use a case-study based approach and focus on three off-grid energy projects: a 110 kW mini-hydro power plant; a 12 kW wind turbine system; and a 1.59 MW solar-diesel hybrid system. We find that end-users primarily see the success or failure of a project in technical terms, but that this narrow conceptualization masks important interactions between technical, economic and institutional factors. We further find that end-user perceptions of newer projects are heavily affected by their perceptions of previous projects. Our findings suggest several ways forward to improve the effectiveness of rural electrification initiatives. Firstly, we should expect complex interactions between technical, economic and institutional factors and build-in the necessary capacity into rural electrification projects to identify and address these interactions. Secondly, there is no one size fits all solution to creating the requisite capacity to deal with interactions among technical, economic and institutional factors. Thirdly, ongoing qualitative or mixed-methods evaluations of rural electrification initiatives can help unravel what would otherwise be hidden interactions between technical, economic and institutional factors.